Contracting-out at Arbitration - Verge, Pierre (Relations industrielles / Industrial Relations, 1963)
Summary A comparative study of arbitral decisions rendered in the United States, the Canadian Common Law Provinces and Quebec over grievances arising in the contest of collective agreements that contain no specific provision on the subject out of Management's action of arranging with an outside firm to have it perform work hitherto done by members of the bargaining unit. The possible effect of new section 10a of the Quebec Labour Relations Act on this practice of contracting out will also be considered.